101k views
0 votes
Find the sum and difference of the following expressions a-b and b-a

User Tommy  Yu
by
5.6k points

2 Answers

2 votes

Answer:

free points

Explanation:

sry i really need points i have like 50

User Msangel
by
5.5k points
7 votes

9514 1404 393

Answer:

  • sum: 0
  • difference: 2a -2b

Explanation:

Sum

(a -b) +(b -a) = a - a + b - b = 0

Difference

(a -b) -(b -a) = a +a -b -b = 2a -2b

User Almeynman
by
4.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.